94 Bridging the divide: senior managers and junior doctors working together. (12th November 2018) - Ali, Omer; Howells, John; Partington, Karen
Abstract : Introduction: The relationship between junior doctors and senior management deteriorated since the 2016 contract dispute. These feelings spilt over to local management, leading junior doctors to feel undervalued and not listened to. This is further compounded by a rise in admissions and workload and rota gaps. Junior doctors often do not have contact with decision makers and are unable to raise their concerns in the same manner as permanent staff. Methods: A group of senior executive attended compulsory foundation year 1 and 2 (FY1/2) doctor teaching. Each executive took part in four or five 10 min roundtable discussions with 7–10 trainees, each had a provocative question. Once all executives have met the whole group, a round up session summarising the most important issues was lead by the foundation programme director. The issues highlighted were then sent the executive to action and report back. This event was jointly organised between junior doctors and executives. Results: Junior doctors were surveyed about their perception of hospital management before the session and afterwards. Using a 1–10 Likert scale, there was an improvement on all outcomes measured. They felt they got to know senior management (2.6 vs 8.1), that they were involved in decision making (3.8 vs 7.0), that managers acted on feedback (4.0 vs 7.2), were transparent (4.4 vs 6.7) and committed to patient safety (6.0 vs 7.7). There was also a rise in juniors recommending the trust as a place to work (7.5 vs 8.8). The two sessions were rated 4.1–4.4 out of 5 with numerous favourable comments, making it one of the most popular sessions on the teaching calendar. Executives are currently being surveyed. Anecdotally they have enjoyed the sessions, felt they gained new insights and the ability to improve the working conditions of junior doctors. Discussion: This project bridged the gap between junior doctors and senior managers, allowing them to discuss their working conditions in a frank and open manner. These were then acted on by the executives who took prompt action, leading to the high satisfaction scores. This closed loop of feedback fosters trust and increases further cooperation leading to improved services overall for patients. The popularity of the sessions shows the effectiveness of bringing together the front liner with senior decision makers. Conclusion: Junior doctors are an invaluable source for quality improvement and strong advocates for improving patient safety. Providing them with a forum to openly discuss issues affecting the frontline with senior decision makers is a powerful tool for improving their working conditions and morale, but ultimately patient safety.